Managing Uncertainty: An Experiment on Delegation and Team Selection - Hamman, John R.; Martínez-Carrasco, Miguel A. (Organization Science, 2023)
We study how organizations use team selection and delegation of authority jointly to navigate uncertain environments. To do so, we model a managerial decision environment in which a manager both determines the skill heterogeneity of the workers and determines whether to retain or delegate the ability to allocate tasks. Delegation enables better-informed workers to allocate tasks more efficiently when uncertainty is high relative to the incentive conflict between manager and worker. Our novel approach allows us to illustrate that this conflict is endogenously determined by the team selection decision. Experimental data support—although not globally—the direction of our theoretical hypotheses and offer insight into how and why choices deviate from expected behavior. Notably, we identify behavioral characteristics that aid decisions along each dimension. Deliberative thinking improves all decisions under low uncertainty and improves team selection regardless of the level of uncertainty. Risk tolerance improves all decisions in highly uncertain situations and helps managers optimally delegate decision rights in all settings. The results highlight potentially costly ways in which managers seek to simplify their decisions but show how deliberative thinking and risk tolerance can improve performance in a complementary manner. History: This paper has been accepted for the Organization Science Special Issue on Experiments in Organizational Theory. Funding: The authors thank Florida State University and the Barcelona Graduate School of Economics for financial support. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/orsc.2021.1545 .